1966
DOI: 10.1115/1.3645902
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Alterations of Rolling—Bearing Steel Undergoing Cyclic Stressing

Abstract: After prolonged cyclic stressing in rolling contact, AISI 52100 bearing steel parts develop extensive regions of microstructural alteration, designated as white etching areas. These are oriented in predictable directions relative to the rolling track. Lenticular carbides are always associated with these areas. Evidence is presented indicating that the boundaries of lenticular carbides constitute planes of weakness which may be preferred planes of fatigue cracking. In the transmission electron microscope the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
2
6

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 0 publications
4
101
2
6
Order By: Relevance
“…14,32,34,38,39,[70][71][72][73][74][75][76][77] Further experiments of this type are likely to yield diminishing value.…”
Section: Hypothesis and Solutionsmentioning
confidence: 99%
“…14,32,34,38,39,[70][71][72][73][74][75][76][77] Further experiments of this type are likely to yield diminishing value.…”
Section: Hypothesis and Solutionsmentioning
confidence: 99%
“…Although having been discussed for several decades, a plausible formation mechanism for DERs is still unavailable. Some authors [5,6] argued that DERs formation results from the over-tempering of martensite, and the fact that DERs have never been observed in the fatigued bearing samples initially tempered to a hardness of around 700 HV [13,17] supports this argument. However, the operation temperatures of bearings, which are usually lower than 100 C, are not sufficiently high to thermally activate the growth of carbides [18], and there is no evidence showing distinct temperature rise in DERs caused by cyclic stressing.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Bush et al [5] found threshold contact pressures below which DERs were never formed, indicating the essential role played by stress. Moreover, the depth range where a DER is formed is considered to be related to the stress state of Hertzian contact, although there is still in disagreement as to the stress component responsible for such phenomenon with some authors [15,19] arguing it is the maximum shear stress, others [13,20] that it is the 45 shear stress, the orthogonal shear stress [5,6] or the vonMises stress [9]. Nevertheless, it was experimentally proved [15] that increasing either contact pressure or operation temperature can accelerate DER formation.…”
Section: Introductionmentioning
confidence: 99%
“…Grundlegende Untersuchungen zur Entstehung der Weißen Bänder (WB) stammen von [8,10,11,12]. Sie stellten bei Lebensdaueruntersuchungen an dem Rillenkugellager 6309 fest, dass -erst nach längeren Laufzeiten -zunächst "flache" und dann "steile weiße Bänder" (FWB und SWB) entstehen (Bild 7).…”
Section: Flache Und Steile Weiße Bä Nder (Fwb Swb)unclassified